Understanding markets with socially responsible consumers - Marc Kaufmann; Peter Andre; Botond Kőszegi (Leibniz Institute for Financial Research SAFE, 2023)
Many consumers care about climate change and other externalities associated with their purchases. We analyze the behavior and market effects of such "socially responsible consumers" in three parts. First, we develop a flexible theoretical framework to study competitive equilibria with rational consequentialist consumers. In violation of price taking, equilibrium feedback nontrivially dampens a consumer's mitigation efforts, undermining responsible behavior. This leads to a new type of market failure, where even consumers who fully "internalize the externality" overconsume externality-generating goods. At the same time, socially responsible consumers change the relative effectiveness of taxes, caps, and other policies in lowering the externality. Second, since consumer beliefs about and preferences over dampening play a crucial role in our framework, we investigate them empirically via a tailored survey. Consistent with our model, consumers are predominantly consequentialist, and on average believe in dampening. Inconsistent with our model, however, many consumers fail to anticipate dampening. Third, therefore, we analyze how such "naive" consumers modify our theoretical conclusions. Naive consumers behave more responsibly than rational consumers in a single-good economy, but may behave less responsibly in a multi-good economy with cross-market spillovers. A mix of naive and rational consumers may yield the worst outcomes.
Keywords: D01; D11; D50; D62; D64; D91; 330; socially responsible consumers; social preferences; climate change; externalities; competitive equilibrium; regulation; taxes; caps